THE HERO’S JOURNEY IN MATTHEW VAUGHN’S MOVIE: KICK-ASS - Oky Irawan Syahputra; Teguh Kasprabowo (Dinamika Bahasa dan Budaya, 2020)
Kick-Ass is a superhero movie. The study aimed to find out about the main character hero’s journey patterns and the characters archetype that occurs in this movie. The data of this study is from watching and analyzed the Kick-Ass movie. This study employed Hero’s Journey from Joseph Campbell to find the patterns with the support from Christopher Vogler for the characters archetype. There are the differences between the hero’s journey Campbell and Kick-Ass movie. In this Study the researcher find 9 stages; The Call to Adventure, Supernatural Aid, The Crossing of the First Threshold, Refusal of the Call, The Meeting with the Goddess, Woman as the Temptress, The Belly of the Whale, Apotheosis and The Ultimate Boon. As for the characters archetype that appearing in this movie are; The Hero, Mentor, Ally, Threshold Guardian, Shape shifter, Trickster and Shadow.